(untitled) (Hoboken, N.J., 2004)
Securitisation has been one of the most exciting developments in fixed-income markets, perfectly illustrating the dynamic and flexible nature of the market itself. The application of securitisation techniques has given rise to "structured finance" securities, which now encompass a wide class of products, each of which deserves separate treatment in its own right. The Handbook of European Structured Financial Products is the first comprehensive guide to this ever-expanding market. The detailed information contained within these pages is aimed at practitioners-including bankers, insurers, and investors-that have an interest in the structured finance of the European debt market. Comprising six information-packed sections, The Handbook of European Structured Financial Products introduces you to many of these products-and the concept of securitisation-while providing practical information and in-depth insight on: ABS and the various assets classes that have been originated as ABS-credit card ABS, consumer loan ABS, auto loan ABS, and much more Whole business securitisation Residential and commercial MBS Cash and synthetic CDOs Structured credit products in the form of credit-linked notes and repackaged transactions
Keywords: Asset-backed financing,Tài sản được hỗ trợ tài chính; Europe,Châu Âu